HIV, HCV, and HBV incidence and residual risk in US blood donors before and after implementation of the 12‐month deferral policy for men who have sex with men. Issue 3 (18th January 2021) - Steele, Whitney R.; Dodd, Roger Y.; Notari, Edward P.; Haynes, James; Anderson, Steven A.; Williams, Alan E.; Reik, Rita; Kessler, Debra; Custer, Brian; Stramer, Susan L.
Abstract: Background: In December 2015, the men who have sex with men (MSM) deferral was reduced to 12 months in the United States. We compared human immunodeficiency virus (HIV), hepatitis C virus (HCV), and hepatitis B virus (HBV) incidence and residual risk before and after this policy change using data from >50% of the US blood supply. Study Design and Methods: Three estimation intervals from the Transfusion‐Transmissible Infections Monitoring System were compared: 15‐months pre‐ and two consecutive, nonoverlapping 15‐month post‐MSM deferral implementation. Repeat, first‐time, and weighted all‐donor incidences were estimated. Residual risk was calculated for all incidence estimates using the incidence/window‐period method. Results: HIV repeat donor incidence was 1.57 per 100 000 person‐years (phtpy) in the second 15‐month post change and not significantly different from pre‐MSM incidence of 2.19 phtpy. Similar values were seen for HCV (1.49 phtpy vs 1.46 phtpy) and HBV (1.14 phtpy vs 0.97 phtpy). In some cases, higher estimated incidence, but without significant change from pre‐MSM to the second post change period occurred for males and first‐time donors (eg, first‐time donors, second post change period: 6.12 phtpy HIV, 6.41 phtpy HCV and 5.34 phtpy HBV). Estimated per donation residual risk was 1:1.6 million for HIV, 1:2.0 million for HCV and 1:1.0 million for HBV based on weighted incidence for all donors. Conclusions: Repeat, first‐time, and overall donor incidence did not vary significantly comparing pre‐MSM to either of the post‐MSM estimation intervals. Residual risk estimates vary by study, but all yield residual risks in the United States of ≤1 per million, and thus far have not shown increasing risk with the 12‐month MSM policy change.